Extended Functional Fixation and Security Around Earnings Announcements: A Reply to Ball and Kothari. - Hand, John R.M. (The Accounting Review, 1991)
Presents a reply to Ray Ball and S.p. Kothari's critique of `A Test of the Extended Functional Fixation Hypothesis,' published in the 1990 issue of the `Accounting Review.' Focus on the firm-size effect on security returns; Critique on the result of the examination of the extended functional fixation hypothesis proposed by the author.